الضوابط الموضوعية والإجرائية لرد المحكم في القانون الأردني: دراسة مقارنة - الطراونة، مصلح أحمد موسى; المجالي، زيد محمد (جامعة مؤتة - عمادة البحث العلمي, 2020)
It is a fundamental principle in arbitration, whether national or international, that every arbitrator must be and remain independent and impartial of the parties and disputes. In addition, an arbitrator bears an ongoing duty of disclosure that requires him/her from the moment that he/she is considered to be sitting as arbitrator until the end of the proceedings to disclose to the parties all circumstances that may give rise to reasonable doubts regarding his/her independence or impartiality. These principles are embodied in Article (15/C) of the Jordanian Arbitration Law No. 31 of 2001 as amended in Law No. (16) of 2018. Disclosure constitutes the cornerstone of the arbitrator's duty to be and remain independent and impartial. This duty is a condition for the validity of the constitution of the arbitral tribunal and a prerequisite for a party's right and power to challenge and disqualify the appointment of the alleged dependent and partial arbitrator. This research examines the independent, impartiality and disclosure duties of an arbitrator through the examination of the disqualification legal regime of the Jordanian arbitration law as set out in Articles 17 and 18 of the Jordanian Arbitration Law No. 31 of 2001 as amended by law No. 16 of 2018. The research deals with the legal action of the disqualification of an arbitrator from both substantive and procedural aspects. It defines the concept of disqualification, identify the concepts of independence, impartiality and disclosure and clarify all procedural requirements of disqualification including: who can submit an application to disqualify an arbitrator? How and to whom should the application be submitted? What are the powers of the arbitral tribunal in relation to the referral of the disqualification application? What are the effects of the Court of Appeal's decision disqualifying an arbitrator on the constitution and the arbitration procedures including the arbitral award?
إن من المبادئ الأساسية التي يقوم عليها نظام التحكيم بنوعيه الداخلي والدولي هو التزام المحكم بالاستقلال والحياد، وكذلك التزامه بالإفصاح عند قبوله مهمته التحكيمية وخلال إجراءات التحكيم عن أي ظروف من شأنها إثارة شكوك معقولة حول حيدته واستقلاله، وقد قنن المشرع الأردني هذه المبادئ في المادة (١٥/ج) من قانون التحكيم الأردني رقم (٣١) لسنة ٢٠٠١ والمعدل بالقانون رقم (١٦) لسنة ٢٠١٨. ويعد التزام المحكم بالإفصاح حجر الزاوية لالتزامه بالاستقلال والحياد، ولذلك فإن تنفيذ هذا الالتزام يعد شرطا لصحة تشكيل هيئة التحكيم، كما ويعد في ذات الوقت شرطا لازما لممارسة كل طرف حقه في طلب رد المحكم المدعي بعدم استقلاله أو عدم حياده. ويتناول هذا البحث التزامات المحكم بالاستقلال والحياد والإفصاح من خلال دراسة النظام القانوني لرد المحكم في القانون الأردني، على النحو الذي فصلته المادتان ١٧ و١٨ من قانون التحكيم الأردني رقم (٣١) لسنة ٢٠٠١ والمعدل بالقانون رقم (١٦) لسنة ٢٠١٨، ويعالج هذا البحث طلب رد المحكم من جميع جوانبه الموضوعية والإجرائية؛ حيث يعرف الرد ويميزه عن غيره من حالات إنهاء مهمة المحكم ويبحث في مفاهيم الاستقلال والحياد والإفصاح تشريعا وفقها وقضاء ويوضح إجراءات الرد من خلال الإجابة على العديد من التساؤلات مثل: من هو صاحب المصلحة والصفة في تقديم طلب الرد؟ كيف ولمن يقدم طلب الرد؟ ما هي سلطات هيئة التحكيم عند تلقيها لطلب الرد وإحالته إلى المحكمة المختصة بالفصل في طلب الرد؟ وما هي الآثار التي تترتب على تقديم طلب الرد وعلى الفصل فيه من قبل محكمة الاستئناف المختصة سواء على تشكيل هيئة التحكيم أو على إجراءات التحكيم بما في ذلك حكم التحكيم النهائي.
Keywords: القانون الأردني -- النظام القانوني -- التشريع الأردني